Formation of Ammonium Nitrate Particles in CO2-rich Atmospheres - Antonio Jiménez-Escobar; Angela Ciaravella; Alfonso Mangione; Cesare Cecchi-Pestellini; Francesco Piazzese; Roberto Candia; Gaspare Di Cicca; Salvatore Varisco (The Planetary Science Journal)
Aerosols play a crucial role in the study of exoplanet atmospheres, as they significantly impact a planet’s climate, albedo, and observational spectra. Understanding aerosol formation and behavior may help in interpreting atmospheric compositions and conditions, providing insights into habitability and atmospheric dynamics. We construct a facility to simulate in the laboratory the effects of lightning discharge on gas mixtures in a controlled setup. In this study, we present experiments performed on gases composed predominantly of carbon dioxide with relatively low amounts of ammonia. Diagnostics using quadrupole mass spectrometry, ultraviolet, and infrared spectroscopy reveal the formation of nitrogen- and oxygen-containing compounds, including nitrates, as well as further oxidation of ammonia to produce solid ammonium nitrate on a cooled substrate. These results highlight the role of electrical discharges in driving atmospheric chemistry, offering insights into potential reaction pathways in exoplanets of similar atmospheric compositions.